Occurrence and transmission of mycovirus Cryphonectria hypovirus 1 from dejecta of Thyreophagus corticalis (Acari, Acaridae). Issue 3 (March 2016) - Bouneb, Mabrouk; Turchetti, Tullio; Nannelli, Roberto; Roversi, Pio Federico; Paoli, Francesco; Danti, Roberto; Simoni, Sauro
Abstract: The natural spread of virus-induced hypovirulence is highly involved in the recovery of blighted chestnut stands and orchards in Italy and in Europe. The potential role of corticolous mites as vectors of hypovirulence in blighted chestnut Castanea sativa (Mill.) stands was pointed out in previous reports. Here, by using RT-PCR, mycovirus Cryphonectria hypovirus (CHV1) was detected in Thyreophagus corticalis mites reared on a hypovirulent strain in monoxenic cultures and in their faecal pellets. Cryphonectria parasitica mycelium derived from mites' dejecta was able to transmit CHV1 to the virulent strain determining its conversion to hypovirulent one. This converted strain induced healing cankers on excised stems, differently from the un-converted virulent strain. Our findings prove the spread of CHV1 by corticolous mites that feed on virus-infected fungus and emphasize their potential role as vectors. Graphical abstract: Highlights: Corticolous mites associated to cankers caused by Cryphonectria parasitica . Thyreophagus corticalis feeds mycelium in hypovirulent C. parasitica monoxenic cultures. Transmission of CHV1 Hypovirus by mites to virulent mycelia in cankers. Virulence decrease in converted virulent strains by mites' fecal pellets.